2008
DOI: 10.5507/bp.2008.040
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-Up of Neoadjuvant-Adjuvant Combination Treatment of Iiia Stage Non-Small-Cell-Lung Cancer: Results of Neoadjuvant Carboplatin/Vinorelbine and Carboplatin/Paclitaxel Regimens Combined With Selective Adjuvant Chemotherapy According to in-Vitro Chemoresistance Test

Abstract: Aim:A prospective study investigated survival of patients with stage IIIA non-small-cell-lung cancer (NSCLC) treated with a combination of neoadjuvant and adjuvant chemotherapy.Methods: Consecutive chemo-naive patients with potentially operable stage IIIA NSCLC received carboplatin-based neoadjuvant treatment. Tumor cells harvested during surgery underwent methylthiazolyl tetrazolium blue (MTT) cytotoxic assay. After surgery, adjuvant chemotherapy was selected, where possible, according to MTT results.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Several studies concerning chemosensitivity tests for lung cancer were previously reported. They used the MTT assay, 14 human tumor clonogenic assay, 15 HDRA, 13,16 differential staining toxicity assay, [17][18][19] adenosine triphosphate (ATP) assay, 20,21 extreme drug resistance assay, [22][23][24] and collagen droplet embedded culture drug sensitivity test (CD-DST). 25,26 Some studies indicated the clinical usefulness of chemosensitivity tests for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies concerning chemosensitivity tests for lung cancer were previously reported. They used the MTT assay, 14 human tumor clonogenic assay, 15 HDRA, 13,16 differential staining toxicity assay, [17][18][19] adenosine triphosphate (ATP) assay, 20,21 extreme drug resistance assay, [22][23][24] and collagen droplet embedded culture drug sensitivity test (CD-DST). 25,26 Some studies indicated the clinical usefulness of chemosensitivity tests for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Some studies indicated the clinical usefulness of chemosensitivity tests for lung cancer. Kolek et al 14 reported that a combination of CBDCA-based neoadjuvant chemotherapy, surgical resection, and adjuvant chemotherapy achieved satisfactory survival rates in stage IIIA NSCLC, especially in patients with the complete resection of the tumor and those given MTT-directed adjuvant treatment and suggested that MTT testing may help optimize adjuvant chemotherapy. Moon et al 21 investigated correlations between the ATP assay and clinical outcomes after ATP assay-guided platinum-based chemotherapy in unresectable NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Je možné také zmínit, že selektivní adjuvantní chemoterapii lze aplikovat na základě vyšetření in vitro rezistence nádorových buněk získaných při operaci. Provedená studie s dlouhodobým mediánem sledování ukázala trend k prodloužení přežití u takto podané chemoterapie [50]. Problémem tohoto přístupu je především náročné zpracovávání nádorových buněk a jejich nehomogenita.…”
Section: Problém Toxicity Dávkové Intenzity a Dokončování Protokolu unclassified